Mathematical model for predicting sludge accumulation in septic tanks based on operational parameters: effect of hydraulic mixing. (20th July 2015) - Al Momani, Fares
Abstract: Reporting sludge accumulation in septic tanks as a constant rate is no longer accepted, and there is a need for a model that predicts sludge accumulation in septic tanks taking into consideration the continuous consumption of sewage solids by microorganisms. This study presents the development of mathematical model that predicts sludge accumulation in septic tanks and to investigate the effect of mixing on solids digestion. The mathematical model takes into consideration the effect of different operational parameters (influent and effluent) as well as the bacterial kinetics in predicting the sludge accumulation in septic tanks. The model predicts with R 2  > 0.88 the sludge accumulation rate in standard septic tank calculated by empirical models developed by Weibel in 1955, and by Bounds in 1995. The model was also used to estimate the typical pump‐out interval for different tank volumes and the sludge accumulation inside septic tanks at different operational parameters.